Peran Lingkungan Belajar dan Media Pembelajaran dalam Menumbuhkan Minat Belajar IPAS Siswa Sekolah Dasar - Mambrasar, Marthina Lilis; Rabia, Supriyati Fatma; Kusumaningrum, Syams (Jurnal Ragam Pengabdian, 2026)
This study aims to describe the role of the learning environment and learning media in fostering students' interest in IPAS (Natural and Social Science) learning among fourth-grade students at SD Negeri Werwaf. The background of this study is the condition of an elementary school in a remote area with limited facilities that is still required to implement the Merdeka Curriculum. This study used a qualitative approach with a case study design. The research subjects were 14 students, one teacher, and the principal. Data were collected through observation, interviews, and documentation. Data analysis employed the Mile & Huberman, while data validity was ensured through source and technique triangulation. The results showed that: (1) the learning environment at school, comprising physical, social, and psychological dimensions, positively fostered students' learning interest; (2) the use of contextual learning media, particularly realia and the natural surroundings of the school, significantly increased students' active engagement in IPAS learning; and (3) the reciprocal relationship between a conducive learning environment and varied local-based media was key to developing students' interest in learning. This study concludes that creativity in optimizing the local environment as a learning resource can effectively foster IPAS learning interest even in schools with limited facilities.